99mTc-RBC SPECT/CT for Duodenal Bleeding Point Detection. (September 2020) - Kang, Seo Young; Moon, Byung Seok; Kim, Hye Ok; Yoon, Hai-Jeon; Kim, Bom Sahn
Abstract : Abstract: This is a case of a 63-year-old man who presented with acute melena and low hemoglobin. Upper and lower gastrointestinal evaluations failed to localize the bleeding focus. 99m Tc-RBC planar scintigraphy identified 2 sites of suspected bleeding in the lower abdomen area. Subsequent SPECT/CT was performed and identified the precise main focus of active bleeding, the second and third parts of the duodenum, and also described the blood accumulation in the jejunum. Esophagogastroduodenoscopy was immediately performed, and results confirmed spurting blood from the small vessel with multiple ulcers in the second part of the duodenum.